Aposthonia guizhouensis sp. nov., a new webspinner of Oligotomidae (Insecta: Embioptera) from China - Chen, Zhi-Teng (Zootaxa, 2022)
Aposthonia guizhouensis sp. nov. from Guizhou Province of China is described and illustrated. The new species is characterized by the distinctive terminalia structure in males. Aposthonia guizhouensis sp. nov. represents the second species of Aposthonia known from China. DNA barcode of the new species is sequenced and compared with its related congeners.